Barbaric Culture and Black Critique : Black Antislavery Writers, Religion, and the Slaveholding Atlantic - Wheelock, Stefan M., 1971- (Book collections on Project MUSE., 2016)
"In an interdisciplinary approach to black antislavery literatures at the dawn of the nineteenth century, Stefan Wheelock shows how the political character of freedom and a religious sensibility allowed Black antislavery writers to countermand ideologies of white supremacy while fostering a sense of racial community and identity. The major figures he selects--Ottobah Cugoano, Olaudah Equiano, David Walker, and Maria Stewart--were principally concerned with ending racial slavery and the slave trade, but they employed antislavery rhetoric at a time when the institution of slavery was preparing progressive Western politics to enter a new phase of imperial and racial domination. This contradictory circumstance, Wheelock argues, poses a significant challenge for understanding the development of this watershed moment in Western political identity. The author looks at the ways in which, during this period, religious and secular versions of collective political destiny both competed and cooperated to forge a vision for a more perfect and just society. What especially captures his interest is how the writers of the African Atlantic deployed religious sensibilities and the call for emancipation as a way of characterizing the liberal foundations of Atlantic political modernity. Although neither "modernity" nor "progress" is a term these writers used, Wheelock contends that a concern with modernity and its liberal character is implicit in their critiques and/or portrayals of the advanced political structures that gave rise to racial enslavement in the first place"--